Poster: BugZoo - A Platform for Studying Software Bugs - Timperley, Christopher Steven; Stepney, Susan; Goues, Claire Le (2018 IEEE/ACM 40th International Conference on Software Engineering: Companion (ICSE-Companion), 2018)
Proposing a new method for automatically detecting, localising, or repairing software faults requires a fair, reproducible evaluation of the effectiveness of the method relative to existing alternatives. Measuring effectiveness requires both an indicative set of bugs, and a mechanism for reliably reproducing and interacting with those bugs. We present BugZoo: a decentralised platform for distributing, reproducing, and interacting with historical software bugs. connects existing datasets and tools to developers and researchers, and provides a controlled environment for conducting experiments. To ensure reproducibility, extensibility, and usability, BugZoo uses Docker containers to package, deliver, and interact with bugs and tools. Adding BugZoo support to existing datasets and tools is simple and non-invasive, requiring only a small number of supplementary files. BugZoo is open-source and available to download at: https://github.com/squaresLab/BugZoo